Implementasi Kurikulum Merdeka Belajar Pada Pembelajaran Akidah Akhlak di Man 1 Medan - Sanfika, Suci; M, Mardianto; Albina, Meyniar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research was motivated by the change in the K13 curriculum to an independent curriculum. Where the independent curriculum is a refinement of the previous curriculum, in this independent curriculum development is strengthened by the development of students’ character. This research aims to determine the planning, implementation, supporting and inhibiting factors of the independent curriculum at MAN 1 Medan.This research uses a qualitative research method with a phenomenological approach. Qualitative research which is field research in the form of qualitative descriptive research, observation, interviews and documentation. The results of this research are that in planning the implementation of the independent learning curriculum in learning moral beliefs, a religious belief teacher must prepare the teaching materials that will be used, namely teaching modules. Not only teaching modules, teachers must also be able to create learning media using LCD projectors and use infrastructure in the learning process. Teachers must also be able to know the characteristics of their students so that the learning process runs well. Then in implementing the independent curriculum, teachers have not fully implemented the independent curriculum during learning.